Medición del impacto de las auditorías ambientales realizadas en la industria maderera ubicadas en el Distrito Metropolitano de Quito durante el periodo 2010 – 2012, utilizando la metodología de la matriz de Clark - Albán López, Carolina Elizabeth (2014)
The present research aims to measure the impact of environmental audits carried out in the timber industries of the Metropolitan District of Quito in the period 2010-2012, at the mention important and concise points so that the user in our thesis has greater understanding about the timber industry. Within the Metropolitan District of Quito, there are companies that are controlled and others that are anonymous, industries that are known there are a total of 120 industries within the population, which I take to research determined, which only uses certifications for its function not environmental audits since they are not obligated by any entity to perform.